FURTHER OBSERVATIONS ON THE INABILITY TO TRANSMIT A RABBIT NEOPLASM BY CELL-FREE MATERIALS - Pearce, Louise (The Rockefeller University Press, 1927)
It has not been possible to propagate a malignant neoplasm of the rabbit with cell-free filtrates, or desiccated tumor tissue or by the use of fluid media kept in contact with tumor tissue. These findings confirm the results of previous experiments carried out with early generations of the tumor. The existence of an agent distinct from the tumor cell which could initiate growth has not been demonstrated. The experiments bring out an essential biological difference between this mammalian neoplasm which is considered to be of epithelial origin and certain filtrable tumors of fowls which have been classified as sarcomata.